Reduce and reuse - Hewitt, Sally, 1949- (London : Franklin Watts., 2008)
Looks at how different types of waste can be reduced and reused, and features brief case studies about kids who are involved in helping to preserve their environment.
Includes bibliographical references (p. 31) and index.
Library Media Connection
Resource Links
Wilson's Children
6.8
3-6.
Keywords: Recycling (Waste, etc.) -- Juvenile literature; Salvage (Waste, etc.) -- Juvenile literature; Waste minimization -- Juvenile literature; Recycling (Waste); Waste minimization; Recycling; Refuse and refuse disposal; Salvage